The Role Of Intolerance Of Uncertainty And Self-Regulation On The Mental Health Conditions Of Educational Staff At Diponegoro University - Endah Kumala Dewi; Kartika Sari Dewi; Yohanis Franz La Kahija (Proceedings of the 1st International Conference on Social Science (ICSS), 2025)
Educational reform in universities requires institutional development, leading to new demands that affect organizational values and employee well-being. Previous studies have revealed that not all changes produce positive results and have a negative impact on the mental health of the staff involved. This study aims to understand the role of Intolerance of Uncertainty IU) and self-regulation in maintaining employee mental health. The subjects of this study consisted of 88 active educational staff, aged 24-60 years, with a minimum of high school education, who have been working since at least 2015. The sampling method used was the convenience sampling method. The instruments used included the Intolerance of Uncertainty Scale (IUS- 12), self regulation scale, HSCL-25 (Indonesian version), and DASS-21 (Indonesian version). The analysis shows a significant role of IU (79%) in the mood disorders of depression and anxiety disorders experienced by the sample group. This study underlines the importance of addressing IU and improving self regulation to support the mental health of educational staff admits organizational change.